Airborne fine particulate matter alters the expression of endothelin receptors in rat coronary arteries. (November 2016) - Xiao, Xue; Cao, Lei; Wang, Rong; Shen, Zhen-xing; Cao, Yong-xiao
Abstract: Exposure to airborne fine particulate matter (PM2.5 ) is associated with cardiovascular diseases. However, a comprehensive understanding of the underlying mechanisms by which PM2.5 induces or aggravates these diseases is still insufficiently clear. The present study investigated whether PM2.5 alters the expression of the endothelin subtype B (ETB ) and endothelin subtype A (ETA ) receptors in the coronary artery and examined the underlying mechanisms. Rat coronary artery segments were cultured with PM2.5 in the presence or absence of MEK/ERK1/2, JNK, and p38 pathway inhibitors. Contractile reactivity was measured by myography. ETB and ETA receptor expression was evaluated using RT-PCR, western blot and immunohistochemistry. Compared with fresh arteries, the cultured coronary arteries showed a significantly enhanced contraction mediated by the ETB receptor and an unaltered contraction mediated by the ETA receptor. Culture with PM2.5 significantly enhanced the contraction and the mRNA and protein expression levels of the ETB and ETA receptors in the coronary arteries, suggesting that PM2.5 induces an upregulation of ETA and ETB receptors. In addition, the PM2.5 -induced increases in ETB - and ETA -mediated vasoconstriction and receptor expressions could be notably decreased by MEK1/2 inhibitor, U0126 and Raf inhibitor, SB386023, suggesting that the upregulation of ETB and ETA receptors is related with MEK/ERK1/2 pathway. In conclusion, PM2.5 induces the ETB and ETA receptor upregulation in rat coronary arteries, and the MEK/ERK1/2 pathway may be involved in this process. Graphical abstract: Highlights: PM2.5 increases ETB - and ETA -mediated contractions in rat coronary artery. PM2.5 increases the mRNA and protein expressions of ETB and ETA receptor in rat coronary artery. MEK1/2 and ERK1/2 inhibitors recede the PM2.5 -induced increases. PM2.5 upregulates ETB and ETA receptors in rat coronary artery via MEK/ERK1/2 pathway. Abstract : PM2.5 induces upregulation of endothelin receptor in rat coronary arteries.